Syair Surat Kapal: The Philosophy of Malay Oral Tradition as Islamic Dawah in Rengat, Riau, Indonesia - Suroyo, Suroyo; Entas, Derinta; Soedjiwo, Novena Ade Fredyarini; Putra, Bima Maulana; Soriente, Antonia; Sibarani, Robert (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2024)
This study explores the philosophical depth embedded in “Syair Surat Kapal,” a cultural artifact from Riau, Indonesia, celebrated for its enchanting poetry and melodious rhythm. The research employs a qualitative methodology within the framework of cultural studies to investigate the philosophy of Islamic Da’wah embodied in the manuscript. The objective of the study is to examine the impact of Islam on “Surat Kapal,” particularly within the context of the oral tradition of the Malay community in Rengat. It traces the influence of Islamic teachings on this community’s oral heritage. This study employs literature review and interviews with seven informants from Riau. The findings of this study underscore the significant role of “Surat Kapal” in shaping the Islamic identity within the community. The underlying philosophy of “Syair Surat Kapal” as a medium for Islamic da’wah is anchored in the belief that literature and poetry are potent mediums for disseminating religious teachings and fostering moral values. The vivid imagery and compelling narrative of the poem in the manuscript not only captivate the audience but also impart significant lessons about faith and belief in God. Consequently, “Syair Surat Kapal” exemplifies the power of literature in religious and cultural propagation within an academic context.